Capability Approach: A Formal Introduction - Dorian Fernando León Tamayo (Journal of Economics and Political Economy, 2017)
The capability approach has been made operable and an example is the Human Development Index and the Multidimensional Poverty Index (Dotter & Klasen, 2014). However, its operable nature in the field of evaluation of specific dimension such as education, gender and poverty from a diffuse perspective is even broader (Addabbo, Di Tommaso & Facchinetti, 2004; Martinetti, 2006; Addabbo & Facchinetti, 2013). In this sense, this article aims to provide a very brief formal aproximation to the capability approach, mainly focusing on some their fundamental concepts.
Additional information: Copyrights Copyright for this article is retained by the author(s), with first publication rights granted to the journal. This is an open-access article distributed under the terms and conditions of the Creative Commons Attribution license (http://creativecommons.org/licenses/by-nc/4.0).
Keywords: I31; I32; D63; 330; Capability approach; Sen's capability approach; Functioning; Amartya Sen